K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

DD
13 tháng 2 2022

\(\left(\frac{1}{2}-1\right)\times\left(\frac{1}{3}-1\right)\times\left(\frac{1}{4}-1\right)\times...\times\left(\frac{1}{200}-1\right)\)

\(=-\left(1-\frac{1}{2}\right)\times\left(1-\frac{1}{3}\right)\times\left(1-\frac{1}{4}\right)\times...\times\left(1-\frac{1}{200}\right)\)

\(=-\frac{1}{2}\times\frac{2}{3}\times\frac{3}{4}\times...\times\frac{199}{200}\)

\(=-\frac{1}{200}\)

13 tháng 2 2022

mình cảm ơn

13 tháng 2 2022

=116,56 nha

HT

13 tháng 2 2022

=3,066666666666666666666667 nha

HT

bằng 3,966666667

13 tháng 2 2022

khó quá!

13 tháng 2 2022

4 con vịt

 

13 tháng 2 2022

lần thứ bnhiu

14 tháng 2 2022

Lần thứ 51

13 tháng 2 2022

Đổi 4,2h = 4h 12'     3,25h = 3h 15'

= ( 3h x 7 + 4h + 3h x 3 - 2h ) + ( 15' x 7 + 12' + 15' x 3 - 12' )

= ( 3h x ( 7 + 3 ) + 4h - 2h ) + ( 15' x ( 7 + 3 ) + 12' - 12' )

= 32h + 150'

= 32h + 2h + 30'

= 34h 30'

HT

13 tháng 2 2022

=34 giờ 30 phút nha

HT

13 tháng 2 2022

quần đảo !!!

13 tháng 2 2022

quần đảo

13 tháng 2 2022

\(\left(-\dfrac{1}{4}+\dfrac{7}{33}-\dfrac{5}{3}\right)-\left(-\dfrac{15}{12}+\dfrac{6}{11}-\dfrac{48}{49}\right)\)

=\(\dfrac{1}{4}+\dfrac{7}{33}-\dfrac{5}{3}+\dfrac{15}{12}-\dfrac{6}{11}+\dfrac{48}{49}\)

=\(\left(-\dfrac{1}{4}-\dfrac{5}{3}+\dfrac{5}{12}\right)+\left(\dfrac{7}{33}-\dfrac{6}{11}\right)+\dfrac{48}{49}\)

\(=\left(-\dfrac{23}{12}+\dfrac{15}{12}\right)+\left(\dfrac{7}{33}-\dfrac{18}{33}\right)+\dfrac{48}{49}\)

=\(-\dfrac{2}{3}+\dfrac{-1}{3}+\dfrac{48}{49}\)

=\(-1+\dfrac{48}{49}=-\dfrac{49}{49}+\dfrac{48}{49}=-\dfrac{1}{49}\)

 

13 tháng 2 2022

\(\left(\frac{-1}{4}+\frac{7}{33}-\frac{5}{3}\right)-\left(-\frac{15}{12}+\frac{6}{11}-\frac{48}{49}\right)\)

\(=\frac{-1}{4}+\frac{7}{33}-\frac{5}{3}+\frac{15}{12}-\frac{6}{11}+\frac{48}{49}\)

\(=\left(-\frac{1}{4}-\frac{5}{3}+\frac{15}{12}\right)+\left(\frac{7}{33}-\frac{6}{11}\right)+\frac{48}{49}\)

\(=\left(-\frac{23}{12}+\frac{15}{12}\right)+\left(\frac{7}{33}-\frac{18}{33}\right)+\frac{48}{49}\)

\(=-\frac{2}{3}+\frac{-1}{3}+\frac{48}{49}\)

\(=-1+\frac{48}{49}\)

\(=-\frac{49}{49}+\frac{48}{49}\)

\(=-\frac{1}{49}\)